Enabling stable MnO2 matrix for aqueous zinc-ion battery cathodes. Issue 42 (23rd October 2020) - Jiao, Yiding; Kang, Liqun; Berry-Gair, Jasper; McColl, Kit; Li, Jianwei; Dong, Haobo; Jiang, Hao; Wang, Ryan; Corà, Furio; Brett, Dan J. L.; He, Guanjie; Parkin, Ivan P.
Abstract : The first study on relationship between the cation pre-intercalation amount in MnO2 matrix and electrochemical performances of AZIBs are provided. Abstract : The primary issue faced by MnO2 cathode materials for aqueous Zn-ion batteries (AZIBs) is the occurrence of structural transformations during cycling, resulting in unstable capacity output. Pre-intercalating closely bonded ions into the MnO2 structures has been demonstrated as an effective approach to combat this. However, mechanisms of the pre-intercalation remain unclear. Herein, two distinct δ-MnO2 (K0.28 MnO2 ·0.1H2 O and K0.21 MnO2 ·0.1H2 O) are prepared with varying amounts of pre-intercalated K + and applied as cathodes for AZIBs. The as-prepared K0.28 MnO2 ·0.1H2 O cathodes exhibit relatively high specific capacity (300 mA h g −1 at 100 mA g −1 ), satisfactory rate performance (35% capacity recovery at 5 A g −1 ) and competent cyclability ( ca. 95% capacity retention after 1000 cycles at 2 A g −1 ), while inferior cyclability and rate performance are observed in K0.21 MnO2 ·0.1H2 O. A stable δ-MnO2 phase is observed upon cycling, with the reversible deposition of Zn4 SO4 (OH)6 ·5H2 O (ZSH), ion migration between electrodes and synchronous transition of Mn valence states. This work firstly and systematically reveals the role of the pre-intercalated ions via density functional theory simulations and show that above a threshold K/Mn ratio of ca. 0.26, the K ions suppress structural transformations by stabilizing the δ phase. To demonstrate its commercial potential, AZIBs with high-loading active materials are fabricated, which deliver adequate energy and power densities compared with most commercial devices.